Determinación de úrea y creatinina sérica pre y post diálisis en pacientes con insuficiencia renal crónica que acuden a la unidad de hemodiálisis del Hospital Teófilo Dávila de Machala. Año 2007 - Mirabá Murgueitio, Leonidas A. (2008)
The present study was carried out at Teófilo Dávila Hospital of Machala city, particularly in patients who are part of the program of hemodialysis that require laboratory service.